Anatomical Study: Anatomical Variations of Dorsalis Pedis Artery and Its Correlation with Clinical Assessment: Anatomical Variations of Dorsalis Pedis Artery and Clinical Assessment - Khatoon, Shehla; Roghani, Faizan Shah; Jan, Rahmat Ullah; Shabnum, Munila; Kamal, Asif; Shah, Syed Mohammad Tahir (Pakistan Journal of Health Sciences, 2026)
The dorsalis pedis artery, the distal continuation of the anterior tibial artery, is a key landmark for pulse assessment, vascular access, and reconstructive procedures of the foot. Its anatomical variability, however, may complicate clinical examination and contribute to diagnostic uncertainty. Objectives: To describe the anatomical configurations and morphometric features of the DPA and to determine how these variations influence clinical pulse palpability. Methods: A descriptive cross-sectional study was conducted at Khyber Medical College, Peshawar, from March 2024 to August 2025, in collaboration with the Radiology Department at Khyber Teaching Hospital. A total of 103 lower limbs were examined through standardized palpation followed by colour Doppler ultrasonography using a 7.5–10 MHz linear transducer. The artery’s origin, course, termination, diameter, and length were documented and classified. Associations between anatomical type and pulse palpability were assessed using Chi-square tests and Cramer’s V. Results: The DPA was present in all limbs. Type I was the most common pattern (80.6%). Variant origins (Types II, IV, V) accounted for roughly one-fifth of cases. A palpable pulse was detected in 88.3% of limbs, with significantly higher palpability in Type I compared with variant types (p<0.001). Pulse palpability did not differ by sex or limb side. Conclusions: Although the DPA generally follows a predictable anatomical course, variations are not uncommon and may reduce clinical pulse detectability. Recognition of these variants is important for accurate vascular assessment, imaging interpretation, and surgical planning.